The influence of task environment and health literacy on the quality of parent-reported ADHD data - Porter, S. C.; Guo, C-Y; Molino, J.; Toomey, S. L.; Chan, E. (Applied Clinical Informatics, 2012)
Objectives: To determine 1) the extent to which paper-based and computer-based environments influence the sufficiency of parents’ report of child behaviors and the accuracy of data on current medications, and 2) the impact of parents’ health literacy on the quality of information produced.Methods: We completed a randomized controlled trial of data entry tasks with parents of children with Attention Deficit Hyperactivity Disorder (ADHD). Parents completed the NICHQ Vanderbilt ADHD screen and a report of current ADHD medications on paper or using a computer application designed to facilitate data entry. Literacy was assessed by the Test of Functional Health Literacy in Adults (TOFHLA). Primary outcomes included sufficient data to screen for ADHD subtypes and accurate report of total daily dose of prescribed ADHD medications.Results: Of 271 parents screened, 194/271 were eligible and 182 were randomized. Data from 180 parents were analyzed. 5.6% parents had inadequate/marginal TOFHLA scores. Using the computer, parents provided more sufficient and accurate data compared to paper (sufficiency for ADHD screening, paper vs. computer: 87.8% vs. 93.3%, P = 0.20; accuracy of medication report: 14.3% vs. 69.4%; p<0.0001). Parents with adequate literacy had increased odds of reporting sufficient and accurate data (sufficiency for ADHD screening: OR 8.0, 95% CI 2.0–32.1; accuracy of medication report: OR 4.4, 95% CI 0.5–37.4). In adjusted models, the computer task environment remained a significant predictor of accurate medication report (OR 18.7, 95% CI 7.5–46.9).Conclusions: Structured, computer-based data entry by parents may improve the quality of specific types of information needed for ADHD care. Health literacy affects parents’ ability to share valid information.
Keywords: Attention deficit disorder with hyperactivity; information science; data collection; quality assurance; patient-provider communications